Peran Komunikasi Partisipatif Relawan Dalam Pengelolaan Posko Bencana Bagi Korban Terdampak Banjir Di Desa Pengkolan Tapanuli Selatan - Zahratu Shafa Pulungan; Aini Zahra; Dian Pina Angraini; Rahmanita Ginting (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the role of participatory communication among volunteers in managing disaster command posts for flood victims in Pengkolan Village, South Tapanuli, and to identify obstacles encountered in its implementation. The study uses a qualitative method with a case study approach. Data were obtained through semi-structured interviews, participant observation, and documentation of three volunteers directly involved in disaster command post management. The results show that participatory communication by volunteers plays an important role through the application of two-way dialogue, active community involvement, equality of roles, adaptation to the local context, and community empowerment in disaster command post management. The implementation of participatory communication still faces obstacles in the form of language and cultural differences, limited communication networks, and differences of opinion in emergency situations. The conclusion of this study confirms that adaptive and empathetic participatory communication can improve the effectiveness of disaster command post management and strengthen the participation and independence of the affected community.